A case of erythrodermia from exacerbated psoriasis vulgaris due to treatment of acute hepatitis C. Issue 1 (December 2016) - Lemmenmeier, Eva; Gaus, Barbara; Schmid, Patrick; Hoffmann, Matthias
Abstract Background Skin side effects during interferon-alpha and ribavirin treatment are common, but autoimmune dermatosis triggered by interferon-alpha is rare. We describe a case of erythrodermia from exacerbated psoriasis during the treatment of acute hepatitis C with pegylated-interferon-alpha and ribavirin. The incidence of psoriasis in this circumstance is unknown and only 36 cases are described in the literature, of which only one describes an erythrodermic psoriasis flare. Case presentation A 50-years old healthy white man presented with the complaints of headache, muscle pain, appetite loss, yellow skin complexion and fatigue. The laboratory results showed elevated liver enzymes above 50 times the upper limit of normal and a positive antibody test and RNA for hepatitis C. A screening test 6 months earlier was negative and therefore the diagnosis of an acute hepatitis C infection was most likely. In the absence of spontaneous clearance of the virus a therapy with pegylated- interferon-α and ribavirin was initiated. After 3 weeks the patient developed red scaly papular skin lesions that evolved despite treatment with prednisone to a severe erythrodermia. A skin biopsy showed typical signs for psoriasis vulgaris. Treatment with steroids was intensified and the hepatitis C therapy stopped. The patient achieved sustained virological response for hepatitis C, but psoriatic lesions were still present 6 months after treatment. Conclusion Although autoimmune skin reactions under pegylated-interferon-α and ribavirin treatment are rare it is important to recognise them early to start an adequate treatment to guarantee hepatitis C treatment continuation.